Implementation Of The Pornography Law On Morality Crimes In Cibinong (Case Study Of Decision Number 136/Pid.B/2023/Pn.Cbi - Fatih, Hanif Nur; Purwoto, Ady; Lestari, Nisa (Universitas Ibn Khaldun Bogor, 2025)
This research examines the implementation of Law Number 44 of 2008 on Pornography in relation to morality crimes, with a case study focus on Decision Number 136/Pid.B/2023/PN.Cbi from the Cibinong District Court. The background of the study arises from the increasing misuse of information technology for distributing pornographic content, which violates moral norms and individual dignity, particularly affecting women. The aim is to analyze Indonesia's legal regulations on morality crimes under the Pornography Law and to review the judge’s legal considerations in the verdict. Using normative legal research methods with statutory and case approaches, data was collected through literature studies and analysis of court documents. The findings indicate that the defendant was proven to have violated Article 35 of the Pornography Law by secretly recording a victim while bathing and sharing the screenshots via WhatsApp status. The court sentenced the defendant to four years in prison and a fine of one billion rupiah. The verdict reflects the application of justice, utility, and legal certainty, although it does not fully embody a progressive legal protection approach for the victim. This study contributes to understanding the effectiveness of Pornography Law enforcement and highlights the need for a more responsive approach to handling technology-based morality crimes.